Endothelial- and Platelet-Derived Microparticles Are Generated During Liver Resection in Humans. (2nd January 2016) - Banz, Yara; Item, Gian-Marco; Vogt, Andreas; Rieben, Robert; Candinas, Daniel; Beldi, Guido
ABSTRACT: Background: Cell-derived plasma microparticles (<1.5 μm) originating from various cell types have the potential to regulate thrombogenesis and inflammatory responses. The aim of this study was to test the hypothesis that microparticles generated during hepatic surgery co-regulate postoperative procoagulant and proinflammatory events. Methods : In 30 patients undergoing liver resection, plasma microparticles were isolated, quantitated, and characterized as endothelial (CD31+, CD41−), platelet (CD41+), or leukocyte (CD11b+) origin by flow cytometry and their procoagulant and proinflammatory activity was measured by immunoassays. Results: During liver resection, the total numbers of microparticles increased with significantly more Annexin V-positive, endothelial and platelet-derived microparticles following extended hepatectomy compared to standard and minor liver resections. After liver resection, microparticle tissue factor and procoagulant activity increased along with overall coagulation as assessed by thrombelastography. Levels of leukocyte-derived microparticles specifically increased in patients with systemic inflammation as assessed by C-reactive protein but are independent of the extent of liver resection. Conclusions : Endothelial and platelet-derived microparticles are specifically elevated during liver resection, accompanied by increased procoagulant activity. Leukocyte-derived microparticles are a potential marker for systemic inflammation. Plasma microparticles may represent a specific response to surgical stress and may be an important mediator of postoperative coagulation and inflammation.